IMAGEWARE SCAN MANAGER APPLICATION IN ARCHIVES MANAGEMENT AT PT ESA TAWANG CIPTA SIDOARJO - Riza Nurkarim (Ebiz Prima Nusa, 2023)
PT Esa Tawang Cipta is a company engaged in education and training in the world of aviation. The company offers education and training packages for aviation security (AVSEC), ground staff and Air Cargo. The prepared instructors have experience in the field of aviation. In addition to the field of education and training, there are other business fields, namely in the field of cargo. Archives are something that cannot be separated from the organization because in it there are sources of information and can also be used as the memory center of a company or organization. In this advanced era, many office work has been done electronically, one of which is archiving. Archives at PT Esa Tawang Cipta still use conventional archives. In the implementation of the archives at PT Esa Tawang Cipta there were problems because the documents in the education and training fields were mixed with the cargo business sector. This makes it difficult to find the archives needed and slows down archiving activities. Therefore, electronic archives to facilitate the implementation of archives in the company. The electronic archive through the IWSM application at PT Esa Tawang Cipta is organized into 3 workgroups, 11 template worksheets, 22 worksheets, 51 fields. In addition, a manual book for running the IWSM application was also made.